EFFECTS OF ADDITION BAGASSE DEGRADANT BY CELLULOLYTIC BACTERIA Bacillus subtilis ON GROWTH MEDIA OF OYSTER MUSHROOM Pleurotus ostreatus - Hibatullah, Juanita; Safitri, Mutia; Harlis, Harlis; Budiarti, Retni Sulistiyoning (BIOPENDIX: Jurnal Biologi, Pendidikan dan Terapan, 2024)
Background: Sugarcane (Saccharum officinarum L.) serves as a valuable resource for the sugar and beverage industries, a significant quantity of its by-product, bagasse, remains underutilized. A promising strategy for increasing the value of bagasse involves improving its substrate quality through the application of cellulose-degrading bacteria, such as Bacillus subtilis. Methods: The objective of this research is to investigate the influence of bagasse degradant supplementation on the growth of oyster mushrooms. A randomized experimental design was employed to evaluate growth media containing varying concentrations of bagasse degradant (500, 600, 700, and 800 gram) in comparison to a control group. The study assessed the impact of bagasse degradant on pin diameter, fresh weight, dry weight, and water content, using ANOVA and the Duncan's Multiple Range Test (DMRT) at a significance level of 5%. Results: The study showed the addition of bagasse degradant affected the pin diameter, fresh weight, and dry weight of oyster mushroom. However, it is not effective towards the water content of oyster mushroom. Conclusion: The addition of bagasse degradant affected the pin diameter, fresh weight, and dry weight, whereas the water composition did not affected the growth of P. ostreatu